(untitled) (SAARC Journal of Agriculture, 2019)
Continuous increase of nitrogen fertilizer use adversely affecting the soil health as well as the environment. It necessitates the systematic study of the impact of nitrogen (N) fertilizer use-reduction on crop yield. In this article, the effects of deep placement of nitrogen fertilizers on nitrogen use efficiency (NUE) and yield of rice variety “BRRI dhan46” were investigated and compared for three N formulations: urea super granule (USG), NPK briquettes and prilled urea (PU). The experiment was conducted in randomized complete block design (RCBD) with eight N treatments replicated three times. The treatments were applied by varying doses (0, 52, 78 and 104 kg ha-1) of nitrogen fertilizers in a known identical soil and weather condition. Applications of PU, USG and NPK briquettes exhibited significant differences on yield attributes of rice. Results revealed maximum grain yield of 6.391 t ha-1 (54% increases over control) for the dose USG 104 kg ha-1 which is statistically similar to the dose USG 78 kg ha-1 and NPK briquettes 104 kg ha-1. The deep placement of USG and NPK briquettes enhanced both the recovery of applied N and N use efficiency compared to broadcast application of prilled urea. However, USG 78 kg ha-1 showed maximum apparent N recovery, N use efficiency, gross margin and marginal benefit-cost ratio. Thus, an application of 78 kg ha-1 USG can be recommended for profitable cultivation of rice variety BRRI dhan46. SAARC J. Agri., 17(1): 93-103 (2019)